Dynamic Ligand Screening by Magnetic Nanoassembly Modulates Stem Cell Differentiation. Issue 2 (14th November 2021) - Hong, Hyunsik; Min, Sunhong; Koo, Sagang; Lee, Yunjung; Yoon, Jinho; Jang, Woo Young; Kang, Nayeon; Thangam, Ramar; Choi, Hyojun; Jung, Hee Joon; Han, Seong‐Beom; Wei, Qiang; et al.
Abstract: In native microenvironment, diverse physical barriers exist to dynamically modulate stem cell recruitment and differentiation for tissue repair. In this study, nanoassembly‐based magnetic screens of various sizes are utilized, and they are elastically tethered over an RGD ligand (cell‐adhesive motif)‐presenting material surface to generate various nanogaps between the screens and the RGDs without modulating the RGD density. Large screens exhibiting low RGD distribution stimulate integrin clustering to facilitate focal adhesion, mechanotransduction, and differentiation of stem cells, which are not observed with small screens. Magnetic downward pulling of the large screens decreases the nanogaps, which dynamically suppress the focal adhesion, mechanotransduction, and differentiation of stem cells. Conversely, magnetic upward pulling of the small screens increases the nanogaps, which dynamically activates focal adhesion, mechanotransduction, and differentiation of stem cells. This regulation mechanism is also shown to be effective in the microenvironment in vivo. Further diversifying the geometries of the physical screens can further enable diverse modalities of multifaceted and safe unscreening of the distributed RGDs to unravel and modulate stem cell differentiation for tissue repair. Abstract : Magnetic screens of various sizes are elastically coupled to RGD‐presenting surfaces with nanogaps. Large magnetic screens exhibiting low RGD distribution stimulate integrin clustering for mechanotransduction‐dependent differentiation of stem cells, which can be dynamically hindered by lowering the nanogaps. Conversely, small magnetic screens facilitate stem cell adhesion and differentiation by dynamically raising the nanogaps.